Predictors of Initial Technical Skill Acquisition in Otorhinolaryngology Residency Applicants. (2nd September 2014) - Gomez, Ernest D.; Bur, Andres; Eliades, Steven J.; Lee, Jonathan M.; Kearney, James J.; Ruckenstein, Michael J.
Abstract : Objectives: (1) Investigate the utility of residency applicant characteristics as predictors of technical skill. (2) Demonstrate the feasibility of technical skill assessment in the residency interview setting. Methods: A cross‐sectional study was performed in December of 2013 to identify residency applicant characteristics that may predict technical skill. During 2 residency interview days, 39 medical students performed up to 5 trials each of 2 box trainer tasks: myringotomy and endoscopic grasping. Subject performance was assessed by an attending surgeon using a global rating scale (GRS). Completion time and error counts were recorded. Applicant factors studied were United States Medical Licensing Examination Step 1 score, Alpha Omega Alpha status, medical school grades, and extracurricular activities. Pearson coefficients and Wilcoxon rank‐sum tests were used to evaluate each applicant characteristic. Results: A total of 117 endoscopic grasping trials and 179 myringotomy trials were assessed. Thirty‐eight of 39 subjects completed both tasks at least 3 times. Participation in competitive sports was associated with more errors during the first endoscopic grasping trial (W = 110.5, P =. 0036) with no difference found in subsequent trials. Step 1 scores and honors grades in core clerkships did not correlate with performance metrics for either task during any trial. Participation in competitive sports did not correlate significantly with task performance for myringotomy. Conclusions: Common methods of residency applicant assessment do not predict performance on otolaryngology‐specific task trainers. It is feasible to measure initial technical skill acquisition in the residency interview setting. It is unknown whether initial technical skill acquisition will correlate with technical skill during residency.